A Genetic and Pharmacological Analysis of Isoprenoid Pathway by LC-MS/MS in Fission Yeast - Takami, Tomonori; Fang, Yue; Zhou, Xin; Jaiseng, Wurentuya; Ma, Yan; Kuno, Takayoshi (PLOS ONE, 2012)
Currently, statins are the only drugs acting on the mammalian isoprenoid pathway. The mammalian genes in this pathway are not easily amenable to genetic manipulation. Thus, it is difficult to study the effects of the inhibition of various enzymes on the intermediate and final products in the isoprenoid pathway. In fission yeast, antifungal compounds such as azoles and terbinafine are available as inhibitors of the pathway in addition to statins, and various isoprenoid pathway mutants are also available. Here in these mutants, treated with statins or antifungals, we quantified the final and intermediate products of the fission yeast isoprenoid pathway using liquid chromatography-mass spectrometry/mass spectrometry. In hmg1-1, a mutant of the gene encoding 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR), ergosterol (a final sterol product), and squalene (an intermediate pathway product), were decreased to approximately 80% and 10%, respectively, compared with that of wild-type cells. Consistently in wild-type cells, pravastatin, an HMGR inhibitor decreased ergosterol and squalene, and the effect was more pronounced on squalene. In hmg1-1 mutant and in wild-type cells treated with pravastatin, the decrease in the levels of farnesyl pyrophosphate and geranylgeranyl pyrophosphate respectively was larger than that of ergosterol but was smaller than that of squalene. In Δerg6 or Δsts1 cells, mutants of the genes involved in the last step of the pathway, ergosterol was not detected, and the changes of intermediate product levels were distinct from that of hmg1-1 mutant. Notably, in wild-type cells miconazole and terbinafine only slightly decreased ergosterol level. Altogether, these studies suggest that the pleiotropic phenotypes caused by the hmg1-1 mutation and pravastatin might be due to decreased levels of isoprenoid pyrophosphates or other isoprenoid pathway intermediate products rather than due to a decreased ergosterol level.